LITERASI MEMBACA DAN JALUR SELEKSI: ANALISIS KEMAMPUAN PEMAHAMAN BACAAN INFERENSIAL MAHASISWA - Muh. Bahly Basri; Iin Nur Yasinta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the inferential reading comprehension skills of students based on university entrance pathways, namely the National Selection Based on Achievement (SNBP), National Selection Based on Tests (SNBT), and the independent pathway. The study used a quantitative approach with a comparative design. Data were collected through an online questionnaire containing a profile form of the university entrance pathways and a multiple-choice test requiring inferential comprehension skills. Respondents were 492 students of the Indonesian Language and Literature Education Study Program from four universities in South Sulawesi. Data were analyzed using descriptive statistics and one-way analysis of variance (ANOVA). The results showed that in general, students' inferential reading comprehension skills were in the moderate category with a mean score of 9.47 (SD = 2.07; maximum score = 15). There were statistically significant differences between the three selection groups. Students from the SNBT pathway had the highest score (M = 9.71; SD = 1.98), students from the SNBP pathway (M = 9.68; SD = 2.06), and students from the independent pathway had the lowest score (M = 8.81; SD = 2.23). These findings imply the need for a systematically designed inferential reading literacy strengthening program.